Case Studies for Teaching Special Needs and at-Risk Students - Buzzell, Judith B.; Piazza, Robert (Delmar Publishers, 1994)
Keywords: Case studies; Case studies; Classroom management; Case studies; Problem solving; Case studies; Teaching; Special education; United States; dept.edu; faculty_collection

Instructor's Guide for Case Studies for Teaching Special Needs and at-Risk Students - Buzzell, Judith B.; Piazza, Robert (Delmar Publishers, 1994)
Keywords: Special education; United States; Classroom management; United States; Problem solving; Teaching; dept.edu

Enquiring Teachers, Enquiring Learners: A Constructivist Approach for Teaching - Fosnot, Catherine Twomey (Teachers College Press, 1989)
Keywords: Elementary school teachers; Training of; United States; Learning, Psychology of; dept.edu; faculty_collection

Songs in Action - Gelineau, R. Phyllis (Parker Pub. Co., 1988)
Keywords: Instruction and study; School music; dept.edu; faculty_collection

Understanding Music Fundamentals - Gelineau, R. Phyllis (Prentice-Hall, 1987)
Keywords: Elementary works; Music; Music theory; Textbooks; dept.edu; faculty_collection

Leading Young Children to Music: A Resource Book for Teachers - Haines, B. Joan E.; Gerber, Linda L. (C. E. Merrill Pub. Co., 1980)
Keywords: Instruction and study; School music; dept.edu; faculty_collection

Educational service centers in Connecticut - Yulo, Frank R. (Connecticut State Dept. of Education, 1977)
Keywords: Connecticut; Teachers; In-service training; Regional Educational Service Centers in Connecticut; Instructional materials centers; Special education; award_winner; dept.edu

Wellsprings of Anticipatory Democracy: An Eco-Systems Preface to the Quality of Life - Clark, Jere W. (Division of Technology and Environmental Education U.S. Office of Education, 1974)
Keywords: Economics; Methodology; Economics; Study and teaching; dept.edu; faculty_collection

Songs in Action - Gelineau, R. Phyllis (McGraw-Hill Book Co., 1974)
Keywords: Instruction and study; Children's songs; School music; dept.edu; faculty_collection

Experiences in Music - Gelineau, R. Phyllis (McGraw-Hill Book Co, 1970)
Keywords: Instruction and study; School music; dept.edu; faculty_collection

The Challenge of Understanding Your Laws - Collins, George J. (Orien, 1968)
Keywords: Law; United States; dept.edu; faculty_collection

On Teaching for World Understanding - Maskel, Anna R. (1965)
Keywords: Children's writings.; dept.edu; faculty_collection

Economic Education Experiences of Enterprising Teachers. - Joint Council on Economic Education (1962)
Keywords: Economics; Study and teaching; dept.edu; faculty_collection

Guiding Children's Arithmetic Experiences: The Experience-Language Approach to Numbers - Hickerson, James Allen (Prentice-Hall education series, 1952)
Keywords: Arithmetic; Study and teaching; dept.edu; faculty_collection

Computing with Meaning and Efficiency: A Manual for Elementary School Teachers - Hickerson, J. Allen (s.n., 1948)
Keywords: Arithmetic; Study and teaching (Elementary); Study and teaching (Primary); Mathematics; dept.edu; faculty_collection

A Helping Hand from the Boss. - Granfield, James; LaFontaine, Hernan (1997)
Keywords: Stress management; dept.edu; faculty_collection

Flexible Scheduling, - Educational Research Council of America Department of In-service Education and Staff Utilization (Educational Research Council of America, 1968)
Keywords: Schedules, School; School management and organization; dept.edu; faculty_collection

Independent Study: An Annotated Bibliography. - Educational Research Council of Greater Cleveland (1966)
Keywords: Bibliography; Independent study; dept.edu; faculty_collection

Reading Evaluation; Appraisal Techniques for School and Classroom - Austin, Mary C. (Ronald Press Co, 1961)
Keywords: Examinations; Reading; dept.edu; faculty_collection

The Preparation of Teachers for the Gifted in the Elementary Schools with Special Reference to Southern Connecticut State College - James, Katherine G. (Thesis Ph. D.--New York University., 1960)
Keywords: Connecticut; Connecticut; Elementary school teachers; Teachers of gifted children; Training of; dept.edu; faculty_collection

The summer stars program - Cantrell, M.L.; Ebdon, S.A.; Firlik, R.; Johnson, D.; Rearick, D. (Educational Leadership, 1997)
Space, futurism, exploration, and stardom are some of the themes at a summer camp inspired by Howard Gardner's theories.
Keywords: dept.bio; dept.edu; peer-reviewed; ⛔ No DOI found

Book Review: Handbook of curriculum evaluation. edited by arieh lewy. new york: longman, inc., 1977. 306pp: - Davis, Harold S (NASSP Bulletin, 1978)
Keywords: book.review; dept.edu

Book Review: A new system of education by b. everard blanchard, homewood, il.: ETC publications, 1975. 154 pp. 8.95 - Davis, Harold S. (The Educational Forum, 1976)
Keywords: book.review; dept.edu

Educational Technology: Instructional Programming and Didakometry by Ake Bjerstedt. New York: Wiley-Interscience, 1972. 300 pp. $9.50. - Davis, Harold S. (Educational Forum, 1974)
Keywords: dept.edu; ⛔ No DOI found

Preparing principals for action, leadership - Davis, Harold S (NASSP Bulletin, 1974)
Both the curricula and methodology of preparing principals is the subject of this article. Describing procedures that work, it will interest principals as well as professors of school administration. © 1974, Sage Publications. All rights reserved.
Keywords: dept.edu

Book Review: Supervision: the reluctant profession by ralph l. mosher and david e. purpel. boston: houghton mifflin co., 1972. 206 pp. 4.95 - Davis, Harold S (The Educational Forum, 1973)
Keywords: book.review; dept.edu

Review of Phi Delta Kappa Fastbacks (Numbers 21-32) - Davis, Harold S (Educational Forum, 1973)
Keywords: dept.edu

Model for Simulation of an Educational Problem - Stambler, M (Educational Technology, 1972)
Keywords: dept.edu; ⛔ No DOI found

Teaching-Learning - Davis, Harold S. (The Educational Forum, 1971)
Ways of Teaching by Ronald T. Hyman. Philadelphia: J. B. Lippincott Company, 1970. 283 pp. $3.95
Keywords: dept.edu

Nucleus of a unified curriculum - Clark, Jere W (Educational technology, 1971)
Keywords: dept.edu; ⛔ No DOI found

Book Review: Principles of skill acquisition edited by e. a. bilodeau with the assistance of ina McD. bilodeau. new york: academic press, inc., 1969. 353 pp. 5.95 - Davis, Harold S (The Educational Forum, 1971)
Keywords: book.review; dept.edu

Book Review: Education and manpower: theoretical models and empirical applications by tore thonstad. edinburgh: oliver & boyd ltd., 1968. 155 pp. 9.25 - Davis, Harold S (The Educational Forum, 1970)
Keywords: book.review; dept.edu

Effect of Compulsory Education and Child Labor Laws on High School Attendance in New-York-City, 1898-1917 - Stambler, M (History of Education Quarterly, 1968)
Keywords: dept.edu

Suburban Students and Their Reading - Wallace, Marion J. (Elementary English, 1966)
Keywords: dept.edu; ⛔ No DOI found

Book Review: Your children need music - greenberg,m - Haines, BJE (Young Children, 1980)
Keywords: book.review; dept.edu; ⛔ No DOI found

Book Review: Infant and toddler programs - a guide to very early-childhood education - cataldo,cz - Thomas, MM (Young Children, 1984)
Keywords: book.review; dept.edu; ⛔ No DOI found

Increasing multicultural understanding: A comprehensive model, 2nd edition. - Torre, CA (Contemporary Psychology, 1999)
Keywords: dept.edu

A dynamical systems perspective on mediating violence in schools: emergent roles of child and youth care workers - Vanderven, Karen; Torre, Carlos Antonio (Child Care Quarterly, 1999)
In recent years, violence has been a major concern for human service professionals and increasingly, to child and youth care workers particularly as they have served in schools where major violent events have occurred. Most often violence prevention and intervention efforts ignore the systemic aspects of violence and are too narrowly focused. This article proposes that a consideration of violence in schools be based on dynamical systems theory. This theory offers rich possibilities for generating a useful model for mediating school violence and for suggesting ways in which child and youth care workers can use their competencies to address the multiple factors related to school violence. The article includes an overview to the concepts of dynamical systems theory, offers the dynamical systems model for mediating school violence and presents implications for the roles and functions of child and youth workers particularly in the emerging area of school based child and youth care work. © 1999 Human Sciences Press, Inc.
Keywords: dept.edu

Ritualizing sacredness in math: profaneness in language arts and social studies. - Ensign, Jacque (The Urban Review, 1997)
This paper examines the effect of ritual in different elementary subjects. Lessons in math, language arts, and social studies were observed in public, private, and home school first and fifth grades. In observing these classes, this researcher noted that in all contexts, math lessons were taught very differently from social studies and language arts, confirming earlier work by Stodalsky. The rituals in how concepts were taught, and in how students and teachers related to each other, were very different in math lessons from in the other two subjects. In language arts and social studies lessons, students and teachers routinely shared personal out-of-school experiences, whereas they rarely did so in math lessons. Drawing on Bernstein's description of the sacredness of subjects and linking it to theories in economic anthropology, the author attempts to explain the isolation of school math and to question the level of intimacy and community in current math classes. © 1997 Human Sciences Press, Inc.
Keywords: dept.edu

Reading and spelling difficulties in high school students: Causes and consequences - Shankweiler, Donald; Lundquist, Eric; Dreyer, Lois G; Dickinson, Cheryl C (Reading and Writing, 1996)
Basic skills in reading and spelling and supporting metalinguistic abilities were assessed in ninth and tenth grade students in two school settings. Students attending a private high school for the learning disabled comprised one group and the other comprised low to middle range students from a public high school. Both the LD students and the regular high school students displayed deficiencies in spelling and in decoding, a factor in reading difficulty that is commonly supposed to dwindle in importance after the elementary school years. Treating the overlapping groups as a single sample, multiple regression analysis was used to investigate the contribution of nonword decoding skill and phonological and morphological awareness to spelling ability. The analysis revealed that decoding was the major component, predicting about half of the variance in spelling. The effect of phonological awareness was largely hidden by its high correlation with decoding, but was a significant predictor of spelling in its own right. Morphological awareness predicted spelling skill when the words to be spelled were morphologically complex. An additional study showed that differences in decoding and spelling ability were associated with differences in comprehension after controlling for reading experience and vocabulary. Even among experienced readers individual differences in comprehension of text reflect efficiency of phonological processing at the word level.
Keywords: Decoding; High school poor readers; Metalinguistic abilities; Spelling; dept.edu

Learning to teach, teaching to learn: the center for constructivist teaching-teacher preparation project. - Fosnot, Catherine Twomey (Teaching Education, 1993)
Keywords: dept.edu

The development of an understanding of balance and the effect of training via stop-action video☆ - Fosnot, Catherine Twomey; Forman, George E; Edwards, Carolyn P; Goldhaber, Jeanne (Journal of Applied Developmental Psychology, 1988)
Children's rule-governed, scientific reasoning in relation to the physical principles involved in balance has been studied by many, for example, Inhelder and Piaget (1958), Karmiloff-Smith and Inhelder (1974), as well as Siegler (1978). Although Siegler criticized the Genevan research on both methodological and conceptual grounds, his work can be criticized for being narrow in scope thus making his data a result of his task and design, rather than a true representation of the rules children employ naturally as they develop an understanding of balance. The work described herein is an attempt to integrate the methodologies of the Piagetian School and Siegler by making use of current video technology to naturalistically assess children's rule-governed behaviors but to also empirically validate them. The first part of this study (N=128, ages 4-9 years) used video to microanalytically assess the strategies children used as they attempted to balance a set of symmetrical, asymmetrical, and weighted blocks on a fulcrum. After validating on ordinal progression of strategies, the study used stop-action video feedback, in a predict-consequence paradigm, to focus reflection on (a) the action of the block, (b) the placement of the block, and (c) the episode in general. A two-way interaction between entering level and type of video feedback was significant. The results are interpreted in terms of Piaget's theory of equilibration suggesting that reflection and cognitive conflict can improve understanding if the child assimilates the feedback to the confirmation or refutation of an initial assimilatory scheme regarding balance. © 1988.
Keywords: dept.edu

The turning point, by fritjof capra - Fosnot, Catherine Twomey (Educational Technology Research and Development, 1986)
Keywords: dept.edu

Media and technology in education: A constructivist view - Fosnot, Catherine Twomey (Educational Technology Research and Development, 1984)
This paper is a version of the seventh ECTJ/ERIC-IR Young Scholar Paper, an annual award initiated to stimulate writing by young professionals in the field of instructional technology. Preparation of the paper was supported by the ERIC Clearinghouse on Information Resources at Syracuse, NY. - Ed. © 1984 Association for Educational Communications and Technology.
Keywords: dept.edu